Immunologically modified enzyme-responsive micelles regulate the tumor microenvironment for cancer immunotherapy. (January 2022) - Han, Zhimin; Gong, Chunai; Li, Juanjuan; Guo, Huanhuan; Chen, Xinlu; Jin, Yangli; Gao, Shen; Tai, Zongguang
Abstract: Immune checkpoint blockade has been proven to have great therapeutic potential and has revolutionized the treatment of tumors. However, various limitations remain, including the low response rate of exhausted T cells and mutual regulation of multiple immunosuppressive cell types that compromise the effect of single-target therapy. Nano-delivery systems can be used to regulate the tumor immune microenvironment in favor of immunotherapy. In this study, we constructed a polypeptide-based micellar system that encapsulates an aryl hydrocarbon receptor (AhR) inhibitor (CH223191) conjugated to T cell activator anti-CD28. The inhibition of AhR activation downregulates the fraction of immunosuppressive cells and effectively inhibits tumor cell metastasis. In addition, the combination with co-stimulatory antibodies improves T-cell activation and synergistically enhances the antitumor effect of AhR inhibitors. The micellar system developed in this study represents a novel and effective tumor immunotherapy approach. Graphical abstract: Image 1 Highlights: Polypeptide-based matrix metalloproteinase (MMP-2)-responsive micelles were constructed. Micelles facilitated the immune regulation of the tumor microenvironment. Induced anti-CD28 and CH223191 had controlled release in response to high MMP-2 level. Aryl hydrocarbon inhibitor reduced the proportion of inhibitory cells.